WOODFORDIA FLORIBUNDA SALISB: A BACKBONE HERB FOR ALL ASAVA AND ARISHTA - Nautiyal, *Rakhi; Chaubey, Suresh; Tiwari, Chityanand (International Journal of Ayurveda and Pharma Research, 2017)
Woodfordia floribunda salisb is a high demand medicinal plant for pharmaceutics and dye industries. Its flowers are highly valued medicinal material used in Indian System of Medicine. The plant is distributed in North-eastern India. This review Woodfordia floribunda salisb, or Fire-flame bush, a plant of Indian origin, is extensively used in folk medicine for the treatment of various ailments. Various parts of this plant possess valuable medicinal properties as anti-inflammatory, anti- tumor, Hepato-protective and free radical scavenging activity, but its flowers are in maximum demand. It is the backbone herb of almost all Asava and Aristha preparations and used as a fermenting agent. Not only to speed up fermentation process in the formation of Asava and Arishta but also Dhataki flowers add colour and taste to them. Dhataki is mainly emphasized in the ancient Ayurvedic texts as one of the most important fermentation product, hence the names Madhyhetu and Madakara. Charak quoted it among the fermentating agents (Asava yoni). He also described Dhataki among the Purisasangrahaniya and Mutraviranjaniya group of drugs. So this review paper is an attempt of the author to provide details of this medicinal plant along with its spectacular properties in fermentation process.